Stock Performance around Share Repurchase Announcements in Germany - Richard Stehle; Udo Seifert (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2003)
Empirical studies of open-market share repurchases in the U.S. typically find a mean abnormal return around the announcement day of about 3%. In Germany share repurchases were highly restricted before May 1998. Since then firms have repurchased shares in the open market more than 250 times. Since the institutional framework differs considerably from the U.S., an analysis of the German data can give important insights. Gerke/Fleischer/Langer (2002), using a larger data set and more carefully chosen procedures than prior studies on German repurchase announcements, presented several puzzling results. We confirm that in Germany the announcement day return is considerably higher than in the U.S. and that this return is higher in Germany?s ?Neuer Markt? than in the traditional market segments. We cannot confirm their findings about bull and bear markets. When we look at subsamples based on the reasons for the repurchase stated in the announcements, we obtain results which are completely different from the results of Gerke/Fleischer/Langer (2002).
urn:nbn:de:kobv:11-10050836
Keywords: G35; 330; Share Repurchase; Ad-Hoc Message; Geldpolitik; Taylor-Regel; Sunspot; Konjunktur; Theorie